Effectiveness of Brassica juncea (Mustard) Plaster on Reduction of Knee Pain and Inability among Geriatrics with Osteoarthritis - D Padma Priya; S Preetha (Journal of Pharmacy and Bioallied Sciences)
Pre-experimental one-group pretest posttest research design was adopted to investigate the effectiveness of Brassica juncea (mustard) plaster on reduction of knee pain and inability among 60 geriatrics with osteoarthritis. The inability was assessed using the Western Ontario McMaster University (WOMAC) Index, which includes 24 parameters under three major headings: joint pain, joint stiffness, and difficulty in performing daily activities, and the severity of pain level was assessed using a numerical pain rating scale. Mustard plaster is applied against the knee for 15 minutes once a day for seven days. On day 8, study participants were re-assessed using the WOMAC Osteoarthritis Index in the interventional group. The pretest mean score of pain was 77.80 ± 5.65, and the posttest mean score was 38.88 ± 11.76. The mean difference score was 38.92. The calculated paired ‘t’ test value of t = 24.428 was statistically significant at P < 0.001 level.